2022
DOI: 10.1177/16878132221089447
|View full text |Cite
|
Sign up to set email alerts
|

Performance enhancement of an evacuated tubes solar collector using Forchheimer’s saturated porous media with embedded nanofluid

Abstract: The evacuated tube solar collector is a proper choice for converting solar energy into heat since it is efficient, practical, and cost-effective. In the current study, the role of nanofluid in porous medium was numerically investigated to improve the performance of a solar collector model and the potential to store energy. The governing equations for the suggested model were solved analytically in the fully developed region using the Forchheimer model. The investigation of the impact on temperature fluctuation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(42 reference statements)
0
0
0
Order By: Relevance
“…Mahdi et al [3] summarized that as the volume concentration of nanoparticles increased, published studies reported a prominent improvement in heat transfer. Duwairi et al [4] showed that the use of nanofluids combined with porous media improves the performance of the evacuated tube when compared to the use of water alone. The nanofluid can be applied to the composite enclosures.…”
Section: Introductionmentioning
confidence: 99%
“…Mahdi et al [3] summarized that as the volume concentration of nanoparticles increased, published studies reported a prominent improvement in heat transfer. Duwairi et al [4] showed that the use of nanofluids combined with porous media improves the performance of the evacuated tube when compared to the use of water alone. The nanofluid can be applied to the composite enclosures.…”
Section: Introductionmentioning
confidence: 99%